Functional Outcomes of Local Pedicle Graft Interpositional Arthroplasty in Adults With Severe Freiberg's Disease. (November 2018) - Abdul, Wahid; Hickey, Ben; Perera, Anthony
Background: Conservative treatment or debridement is generally sufficient for Freiberg's disease grades I and II but operative intervention for the late stages of the disease process (III-V) is more challenging. Debridement alone is not sufficient and various forms of arthroplasty have been put forward. We have evaluated the outcomes of patients treated with an interpositional arthroplasty technique using a pedicle graft of periosteum and fat made into a "Rollmop" spacer for severe Freiberg's disease. No results have previously been reported for this technique. Methods: Twenty-five consecutive cases (23 patients) were performed from February 2009 to September 2016 (20 females, 5 males). Mean age at surgery was 52.6 years (range 19-70.5 years) with 92% affecting the second metatarsal. Twenty-three were primary cases and 2 were revision cases. Five cases were stage III, 12 were stage IV, and 8 were stage V. All patients underwent interpositional arthroplasty using a periosteum and fat pedicle graft from the affected metatarsal shaft as described by Myerson. Patients were evaluated using Manchester-Oxford Foot Questionnaire (MOXFQ) and American Orthopaedic Foot & Ankle Society Questionnaire (AOFAS). Mean follow-up was 3.5 years (0.6-7.6 years). Paired 2-tailed Student t tests were used to assess clinical significance. Results: Surgery allowed 8 patients to return to normal footwear, 10 patients returned to fashion footwear/heels, and 5 returned to sports. Nineteen cases (17 patients) were assessed with patient-reported outcome measures and all showed a clinically and statistically significant improvement in their scores. Mean pre- and postoperative VAS pain scores were 6.2 (range 4-9) and 1.8 (range 0-6) ( P < .05). Mean perioperative AOFAS scores were 45.6 (range 15-73) and 82.7 (range 57-100) ( P < .05). Mean perioperative MOXFQ scores were 60.0 (range 23-89) and 18.1 (range 0-80) ( P < .05). Conclusion: This novel interpositional arthroplasty technique using a "rollmop" of periosteum and fat for severe Freiberg's disease produced significant improvements in pain, functional outcome, and patient satisfaction without donor site morbidity. Furthermore, it allowed patients to return to desired footwear and sporting activities. The functional outcome and joint range of motion was superior after a K-wire was no longer placed across the joint, and we believe it is essential to avoid this to permit early range-of-motion exercises. Level of Evidence: Level IV, retrospective case series.